2018
DOI: 10.1002/solr.201700215
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Alkylammonium Spacer Cations for Efficient Two‐Dimensional Perovskite Solar Cells with Enhanced Moisture and Thermal Stability

Abstract: Three‐dimensional (3D) perovskite solar cells are prone to degradation in the presence of moisture, heat, and light. Recently, two‐dimensional (2D) perovskites are synthesized by isolating metal halide perovskite layers using aliphatic or aromatic alkylammonium spacer cation, which can retain their performance under ambient humidity levels due to the hydrophobic property of the spacer cation. However, the best 2D perovskite thus far, using aliphatic short butylammonium (BA) cation as spacer cation, shows only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 56 publications
(92 reference statements)
2
31
0
Order By: Relevance
“…Metal halide perovskites have emerged as a promising photovoltaic technology due to their solution processibility, low fabrication costs, high power conversion efficiency and rapid energy payback time [1][2][3][4][5][6] . Due to excellent light absorption, devices.…”
Section: Introductionmentioning
confidence: 99%
“…Metal halide perovskites have emerged as a promising photovoltaic technology due to their solution processibility, low fabrication costs, high power conversion efficiency and rapid energy payback time [1][2][3][4][5][6] . Due to excellent light absorption, devices.…”
Section: Introductionmentioning
confidence: 99%
“…22,[29][30][31] From the commercialization of perovskite-based solar cell technology point of view, there is an urgent need to improve the stability of the perovskites in the near future. In literature, there are very few 2D perovskite materials reported that are stable under humid conditions, 29,32,33 thermal stress [34][35][36] and continuous illumination to UV light. 29 The quest to develop a stable perovskite material that can outperform under ambient conditions has motivated us to investigate the long carbon chain (C 14 , C 16 and C 18 ) organic cations in 2D perovskite.…”
Section: Introductionmentioning
confidence: 99%
“…Organolead halide perovskite materials have been used as the active material in a range of optoelectronic device based applications such as light emitting devices, photodetectors etc. However, the understanding of the fundamental material properties of organolead halide perovskite and device operation in varied humidity is still limited . Commercialization of organolead halide perovskite‐based solar cells is very challenging due to their associated stability issues (thermal/photo/moisture/oxygen) despite remarkable efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…However, the understanding of the fundamental material properties of organolead halide perovskite and device operation in varied humidity is still limited. [14][15][16] Commercialization of organolead halide perovskite-based solar cells is very challenging due to their associated stability issues (thermal/ photo/moisture/oxygen) despite remarkable efficiency. [17][18][19][20] Recently, a protective hole transport material (HTM) has been utilized to prevent atmospheric moisture from entering the perovskite film, which leads to enhanced stability.…”
Section: Introductionmentioning
confidence: 99%